Splitting force of bottle-shaped struts with different height-to-width ratios. (15th July 2018) - Yuan, Aimin; Xu, Donghui; Qian, Shoulong; Dai, Hang
Highlights: A new quantitative CDM is established for describing the equation of ILCs. Splitting force formulae with different height-to-width ratios are obtained. These derivation formulae are validated using test data and FEA results. Abstract: A bottle-shaped strut is a common kind of strut in the structures, whose compression disperses, resulting in a splitting force at some distance away from the load plate. Considering characters of the geometric and physical boundary conditions which are different from previous studies, a new mathematical equation for the infinite isostatic lines of the compression (ILC) is obtained and a corresponding equation of transverse stresses distribution is derived. Then theoretical formulae to calculate the resultant splitting forces and their location in a bottle-shaped strut are proposed. Based on the principle of superposition, different compression dispersion models for the struts with different height-to-width ratios are individually formulated and simplified. A recommendation for EN1992 is presented. The transverse stresses distribution and the equations for the resultant splitting force and their locations are validated by the test and FEM results. The results show that the proposed equations have good agreements with the test and FEM result, which can provide accurate predictions for the magnitude and location of the resultant splitting force.